Patient‐Adaptive Magnetic Resonance Oximetry: Comparison With Invasive Catheter Measurement of Blood Oxygen Saturation in Patients With Cardiovascular Disease. Issue 5 (1st May 2020) - Varghese, Juliet; Smyke, Matthew; Pan, Yue; Rajpal, Saurabh; Craft, Jason; Potter, Lee C.; Raman, Subha V.; Ahmad, Rizwan; Simonetti, Orlando P.
Abstract : Background: The current standard method to measure intracardiac oxygen (O2 ) saturation is by invasive catheterization. Accurate noninvasive blood O2 saturation by MRI could potentially reduce the duration and risk of invasive diagnostic procedures. Purpose: To noninvasively determine blood oxygen saturation in the heart with MRI and compare the accuracy with catheter measurements. Study Type: Prospective. Subjects: Thirty‐two patients referred for right heart catheterization (RHC) and five healthy subjects. Field Strength/Sequence: T2‐prepared single‐shot balanced steady‐state free‐precession at 1.5T. Assessment: MR signals in venous and arterial blood, hematocrit, and arterial O2 saturation from a pulse oximeter were jointly processed to fit the Luz–Meiboom model and estimate blood O2 saturation in the right heart. Interstudy reproducibility was evaluated in volunteers and patients. Interobserver reproducibility among three readers was assessed using data from volunteers and 10 patients. Accuracy of MR oximetry was compared to RHC in all patients. Statistical Tests: Coefficient of variation, intraclass correlation coefficient, Bland–Altman analysis, Pearson's correlation. Results: The coefficient of variation for interstudy reproducibility of O2 saturation was 2.6% on average in volunteers and 3.2% in patients. Interobserver reproducibility among three observers yielded intraclass correlation coefficients of 0.81 and 0.87 respectively for RV and MPA O2 saturation. O2 saturation (y = 0.85x + 0.13, R = 0.78) and (a‐v)O2 difference (y = 0.71x + 0.90, R = 0.69) by MR and RHC were significantly correlated ( N = 32, P < 0.05 in both cases) in patients. MR slightly overestimated O2 saturation compared to RHC with 2% ± 5% bias and limits of agreement between −7% and 12%. Data Conclusion: MR oximetry is repeatable and reproducible. Good agreement was shown between MR and catheter venous O2 saturation and (a‐v)O2 difference in a cohort whose venous O2 ranged from abnormally low to high levels, with most values in the normal physiological range. Level of Evidence: 2. Technical Efficacy Stage: 2.